2023
DOI: 10.1007/s00025-023-01859-w
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Flat Functions in Carleman–Roumieu Ultraholomorphic Classes in Sectors

Abstract: We construct optimal flat functions in Carleman–Roumieu ultraholomorphic classes associated to general strongly nonquasianalytic weight sequences, and defined on sectors of suitably restricted opening. A general procedure is presented in order to obtain linear continuous extension operators, right inverses of the Borel map, for the case of regular weight sequences in the sense of Dyn’kin. Finally, we discuss some examples (including the well-known q-Gevrey case) where such optimal flat functions can be obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…to simplify arguments. More precisely, in [ 6 , Lemma 3.18] it has been shown that even which clearly implies . We write if ( 2.6 ) holds for the corresponding sequences of quotients , .…”
Section: Weights and Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…to simplify arguments. More precisely, in [ 6 , Lemma 3.18] it has been shown that even which clearly implies . We write if ( 2.6 ) holds for the corresponding sequences of quotients , .…”
Section: Weights and Conditionsmentioning
confidence: 98%
“… Note that for all j does not hold automatically for all sequences belonging to the set . However, when given , then we can always find such that M and are equivalent and such that the corresponding sequence of quotients is strictly increasing, see [ 6 , Lemma 3.18]. This formal switch allows to avoid technical complications resp.…”
Section: Weights and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation